Current application and future perspectives of antimicrobial degradable bone substitutes for chronic osteomyelitis - Jiang, Chenxi; Zhu, Guangxun; Liu, Qian (Frontiers in Bioengineering and Biotechnology, 2024)
Chronic osteomyelitis remains a persistent challenge for the surgeons due to its refractory nature. Generally, treatment involves extensive debridement of necrotic bone, filling of dead space, adequate antimicrobial therapy, bone reconstruction, and rehabilitation. However, the optimal choice of bone substitute to manage the bone defect remains debatable. This paper reviewed the clinical evidence for antimicrobial biodegradable bone substitutes in the treatment of osteomyelitis in recent years. Indeed, this combination was proved to eradicate infection and facilitate bone reconstruction, which might reduce the cost and hospital stay. Handling was associated with increased risk of unwanted side effect to affect bone healing. The study provides some valuable insights into the clinical evaluation of treatment outcomes in the aspects of infection eradication, bone reconstruction, and complications caused by materials. However, achieving complete infection eradication and subsequently perfect bone reconstruction remains challenging in compromised conditions, hence advanced innovative bone substitutes are imperative. In this review, we mainly focus on the desired functional effects of advanced bone substitutes on infection eradication and bone reconstruction from the future perspective. Handling property was optimized to simplify surgery process. It is expected that this review will provide an important opportunity to enhance the understanding of the design and application of innovative biomaterials to synergistically eradicate infection and restore integrity and function of bone.